Diagnostic performances of Schistosoma haematobium and Schistosoma mansoni recombinant proteins, peptides and chimeric proteins antibody based tests. Systematic scoping review. - Arthur Vengesai; Victor Muleya; Herald Midzi; Tryphine Vimbai Tinago; Isaac Chipako; Marble Manuwa; Thajasvarie Naicker; Takafira Mduluza (PLoS ONE)
Background Traditional diagnostic tests for schistosome infections are suboptimal, particularly when the parasite burden is low. In the present review we sought to identify recombinant proteins, peptides, and chimeric proteins with potential to be used as sensitive and specific diagnostic tools for schistosomiasis. Methods The review was guided by PRISMA-ScR guidelines, Arksey and O'Malley's framework, and guidelines from the Joanna Briggs Institute. Five databases were searched: Cochrane library, PubMed, EMBASE, PsycInfo and CINAHL, alongside preprints. Identified literature were assessed by two reviewers for inclusion. A narrative summary was used to interpret the tabulated results. Results Diagnostic performances were reported as specificities, sensitivities, and AUC. The AUC for S. haematobium recombinant antigens ranged from 0.65 to 0.98, and 0.69 to 0.96 for urine IgG ELISA. S. mansoni recombinant antigens had sensitivities ranging from 65.3% to 100% and specificities ranging from 57.4% to 100%. Except for 4 peptides which had poor diagnostic performances, most peptides had sensitivities ranging from 67.71% to 96.15% and specificities ranging from 69.23% to 100%. S. mansoni chimeric protein was reported to have a sensitivity of 86.8% and a specificity of 94.2%. Conclusion The tetraspanin CD63 antigen had the best diagnostic performance for S. haematobium. The tetraspanin CD63 antigen Serum IgG POC-ICTs had a sensitivity of 89% and a specificity of 100%. Peptide Smp_150390.1 (216-230) serum based IgG ELISA had the best diagnostic performance for S. mansoni with a sensitivity of 96.15% and a specificity of 100%. Peptides were reported to demonstrate good to excellent diagnostic performances. S. mansoni multi-peptide chimeric protein further improved the diagnostic accuracy of synthetic peptides. Together with the advantages associated with urine sampling technique, we recommend development of multi-peptide chimeric proteins urine based point of care tools.